Microbiota boost immunotherapy? A meta-analysis dives into fecal microbiota transplantation and immune checkpoint inhibitors - Anqi Lin; Lihaoyun Huang; Aimin Jiang; Lingxuan Zhu; Weiming Mou; Yu Li; Chunyan Zhang; Zaoqu Liu; Jian Zhang; Quan Cheng; Ting Wei; Peng Luo (BMC Medicine)
Abstract Background Immune checkpoint inhibitors (ICIs) are a cornerstone of modern cancer treatment, but their effectiveness is limited. Fecal microbiota transplantation (FMT), which alters the gut microbiome, has shown promise in enhancing ICIs’ therapeutic effects. Methods We conducted a comprehensive search of relevant studies available up to September 30, 2024, to analyze the clinical efficacy and safety of combining FMT with ICIs in cancer treatment. The primary endpoint was the objective response rate (ORR), with secondary evaluations of survival outcomes and safety. Results A total of 10 studies involving 164 patients with solid tumors were included. The pooled ORR was 43% (95% CI: 0.35–0.51). Subgroup analysis revealed that the combination of anti-PD-1 and anti-CTLA-4 therapies was associated with a significantly higher ORR (60%) compared to anti-PD-1 monotherapy (37%; P = 0.01). The incidence of grade 1–2 adverse events (AEs) was 42% (95% CI: 0.32–0.52), while grade 3–4 AEs occurred in 37% of patients (95% CI: 0.28–0.46). Conclusions This meta-analysis provides preliminary evidence supporting the use of FMT as a strategy to enhance the efficacy of ICIs in patients with advanced or refractory solid tumors. However, larger-scale randomized controlled trials with long-term follow-up are required to confirm and optimize treatment protocols.